Watersheds in Marxist Ecofeminism. - Odih, Pamela (Cambridge Scholars Publishing, 2014)
The neoliberal environmental governance of river conservation, coupled with the organizational modernization imposed and sustained by the European Union's water directives, engenders Other Spaces of feminist ecological alignment. The riparian landscapes of urban cities are manifestations of political and ideological rationalities operating under the constraints of capitalist markets, and are saturated by the contradictions of neoliberal environmental science. Neoliberal rationalities configur ...